BIOSENSORS - A NOVEL TECHNOLOGY FOR RAPID AND ON-SITE PLANT PATHOGEN DIAGNOSTICS (Journal of Plant Disease Sciences, 2025)
Timely and accurate detection of plant pathogens is essential to safeguard global food production, particularly in the context of emerging diseases and climate-induced agricultural vulnerabilities. Conventional diagnostic techniques such as enzyme-linked immunosorbent assay (ELISA), polymerase chain reaction (PCR), and loop-mediated isothermal amplification (LAMP), although effective under laboratory conditions, are often constrained by high costs, extended processing times, and limited field portability. In this context, biosensor technology has emerged as a promising alternative, enabling rapid, sensitive, and on-site detection of plant pathogens with minimal technical requirements.This review examines the evolution, historical development, and recent advances in biosensor-based diagnostics for plant disease detection. Various biosensor platforms, including antibody-based, DNA-based, optical, and electrochemical biosensors, are discussed. These devices utilize molecular recognition mechanisms that convert biological interactions into measurable signals through techniques such as impedance spectroscopy, surface plasmon resonance, and colorimetric assays. Special emphasis is placed on the incorporation of nanomaterials, including gold nanoparticles, quantum dots, and carbon nanotubes, which significantly enhance detection sensitivity, signal transduction, and probe stability. Despite notable progress, several challenges remain, such as analyte interference, limited multiplexing capability, and the need for robust field validation. Nevertheless, ongoing innovations in microfluidics, portable sensing platforms, and artificial intelligence-integrated diagnostics are expected to accelerate the adoption of biosensors in plant disease surveillance. The integration of biosensor technologies into agricultural monitoring systems supports early disease intervention, reduces reliance on chemical inputs, and represents a critical step toward sustainable, data-driven, and resilient farming practices.
Keywords: Biosensors, Disease surveillance, Integrated disease management (IDM), Nanobiosensors, On-site diagnostics Plant pathogen detection,